Upper Gastrointestinal Symptoms in Medical Professionals: A Higher Burden?. Issue 1 (January 2015) - Barkin, Jodie A.; Sendzischew, Morgan A.; Landy, David C.; Moshiree, Baharak
Abstract : Objectives: Gastroesophageal reflux disease (GERD) and dyspepsia cause significant healthcare resource utilization and greatly affect quality of life; therefore, a tendency exists to self-treat in lieu of formal diagnosis. Although their prevalence is established in the general population, their prevalence in physicians remains unknown. Our aim was to estimate the prevalence of GERD and dyspepsia symptoms in a sample of medical professionals by level of training. Methods: An anonymous, computer-based questionnaire was distributed to medical students, residents/fellows, and attending physicians at our institution. The survey included symptom-based questions for GERD (Reflux Disease Questionnaire); quality-of-life questionnaire for dyspepsia (Nepean Dyspepsia Index [NDI]), and the Gastroparesis Cardinal Symptom Index (GCSI). We calculated scores based on the validated system from each questionnaire and used appropriate statistical analysis to evaluate associations between symptomatology and training level (medical students, residents/fellows, and attending physicians). Results: Overall, there were 327 respondents (155 medical students, 127 residents/fellows, 45 attending physicians), of whom 52% were women, 56% were white non-Hispanic, 19% were Hispanic, and 74% were born in the United States/Canada. A total of 21% reported previously diagnosed GERD/dyspepsia, and 42% reported previously or currently using a medication for GERD/dyspepsia, with significantly higher use of proton pump inhibitors in attending physicians than in medical students and residents/fellows ( P < 0.01). Higher median total scores for the NDI ( P = 0.01) and GCSI ( P < 0.01) in medical students exist compared with residents/fellows and attending physicians, with no significant differences for the Reflux Disease Questionnaire among groups. Conclusions: Although the prevalence of diagnosed GERD/dyspepsia in our sample was comparable to the general population, medication use was higher. Self-treatment with prescription medications increased with training. Median NDI and GCSI scores were inversely related to training level, which may reflect self-treatment in medical professionals with advanced training. Further study of GERD/dyspepsia in medical professionals is warranted. Abstract : Gastroesophageal reflux disease (GERD) and dyspepsia cause significant healthcare resource utilization and greatly affect quality of life. GERD and dyspepsia prevalence are established in the general population; however, prevalence amongUS physicians remains unknown. This article estimates the prevalence ofGERD and dyspepsia symptomatology in a sample of medical professionals by level of training, from medical students to residents/fellows to attending physicians.Although the prevalence of diagnosed GERD/dyspepsia in the authors'sample was comparable to the general population, medication use was higher. Self-treatment with prescription medications increased with amount of training.